Role of Ayurveda in Functional Neurorehabilitation of a Child with Occipital Encephalocele and Arnold–Chiari Malformation: A Case Study - Anirudhan, Roshni; G, Arathi; Prasad , Aparna (Journal of Neonatal Surgery, 2025)
Background: Occipital encephalocele, a post-neurulation neural tube defect, is associated with high rates of neurological impairment and developmental delay despite timely surgical correction. Conventional neurosurgical management primarily addresses the structural defect, often leaving persistent functional deficits that demand long-term rehabilitative strategies. Case Presentation: We report the case of a 3-year-old female child born with occipital meningoencephalocele, type II Arnold–Chiari malformation, and syringomyelia, who underwent surgical repair during infancy. Postoperatively, she presented with spasticity of the lower limbs and left upper limb, cortical fisting, bilateral visual and auditory deficits, and global developmental delay affecting motor, language, and cognitive milestones. Ayurvedic Intervention: The clinical history was interpreted as Abhyantara Vidradhi complicated by post-surgical Kapha-Vāta Āvaraṇa. Management included Āma Pachana and Srotoshodhana herbal formulations, followed by external therapies tailored for Kapha-Vāta Śamana. Swedana-based interventions resulted in reduced spasticity and improved trunk control, enabling unsupported sitting for 2–3 minutes. Functional outcomes assessed by the Gross Motor Function Measure (GMFM) improved from 11.04% pre-treatment to 27.08% post-treatment. Brimhana, Medhya, and Rasāyana interventions were subsequently introduced to promote neuromuscular and cognitive development. Conclusion: This case demonstrates the potential of integrative Ayurvedic rehabilitation in enhancing functional outcomes and neurodevelopmental progress in children with congenital brain malformation sequelae. While surgical intervention remains the cornerstone of structural correction, adjunctive Ayurvedic therapies may contribute significantly to neuroplasticity, motor recovery, and overall quality of life. Further systematic studies are warranted to validate these findings